A Conceptual Study and Significance of Oja According to Ayurveda - Yadav, Indiwar; Kadu, Smita; Verma, Sanjay Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda, renowned as the science of life, is dedicated to preserving the well-being of living organisms by both preventing and treating illnesses. Central to Ayurvedic treatment (Chikitsa) is principles outlined in its literature, including the concepts of Ojas and Vyadhikshamatva. Ojas, situated in the heart (hridaya), extend throughout the body, governing its processes. The presence of Ojas is fundamental for the sustenance of life, aligning various bodily states, and preventing destruction. This principle is crucial in the body’s defense against disease-causing agents, halting pathogenesis. Ayurvedic literature explicates Ojas as essence of all Dhatus, representing Bala (strength) of each body part. Ojas is likened to Bala, providing physical, mental, and immunological resistance against ailments. Vyadhikshamatva, the body’s capacity to ward off illness, parallels the contemporary concept of immunity in science. Ojas, as a vital force, ensures the body’s survival and alignment of various states when present. It serves as the cornerstone for the body’s resilience against diseases. Vyadhikshamatva, akin to modern immunity, safeguards against harmful infections. The alignment of Ayurvedic principles with contemporary scientific concepts establishes the relevance of Ojas and Vyadhikshamatva in maintaining health and preventing diseases. Recognizing Ojas as the essence of Dhatus underscores its role in physical, mental, and immunological strength. Incorporating these principles into health applications, particularly in addressing immune disorders, can offer holistic approaches in line with Ayurvedic wisdom. Understanding and harnessing Ojas and Vyadhikshamatva could prove instrumental in developing Ayurvedic remedies for enhancing immunity, promoting overall well-being.